(untitled) (Zbornik Pravnog fakulteta Sveučilišta u Rijeci, 2022)
For victims of domestic violence, obligatory lockdowns aimed at preventing the spread of COVID-19 have trapped them inside the home with their abusers 24 hours a day and isolated them from the people and resources that could help them. Due to the countrywide lockdown, the abusers are continuously present in the victims’ lives and have a greater ability to terrify them and control their lives. Home has become a double-edged sword for the victims of domestic violence – the safest place from the Coronavirus and the most dangerous place because they are isolated with their abusers. This research aims to explore how COVID-19 social restrictions have affected the occurrence of violence against closely related persons in Croatia. To this end, police data will be compared and analysed on the number of reported cases of violence committed to the detriment of a closely related person during the lockdown period and immediately before and after it. Special attention will be paid to the qualification of criminal offences committed against a closely related person and to the sociodemographic characteristics of perpetrators and victims of that violence. Based on the interpretation of the data, we assess whether significant discrepancies in the cases of family violence committed during lockdown can be detected. The conclusion points to certain shortcomings in the manner of monitoring the trend of violence among closely related persons in Croatia and the need to address this phenomenon systematically and comprehensively.